Meminimalkan Ketergantungan Peserta Didik pada Aplikasi Photomath dengan Merubah Soal Matematika Menjadi Bentuk Teks - Nurkhayati Puji Rahayu (Action Research Journal, 2022)
This study aims to determine how much students depend on photomath applications, find out how much decrease in students' dependence on photomath applications, and minimize student dependence on photomath applications. The place of this research is SMA Negeri 1 Karangrayung, Grobogan Regency. The subjects in this study were all students of class XI MIPA in the academic year 2021/2022, with a total of 144 students consisting of 40 males and 104 females. The implementation method in this research is to compare the data on the initial condition of students' dependence on the photomath application with the data on the final condition of the students' dependence on the photomath application. Data on the initial condition of students' dependence on the photomath application were obtained from questionnaires given to students before the teacher changed math problems into text form. Meanwhile, data on the final condition of students' dependence on the photomath application were obtained from questionnaires given to students after the teacher changed math problems into text form. The results of this study indicate that the percentage of students' dependence on the photomath application which was initially at the initial condition was 62.50%, then in the final condition became 19.44%. While the percentage of students who are not dependent on the photomath application which was originally in the initial condition was 37.50% and in the final condition it became 80.56%. These results prove that how to convert math problems into text form can minimize students' dependence on photomath applications in class XI MIPA SMA Negeri 1 Karangrayung in 2022.